Mechanism of Improved Luminescence Intensity of Ultraviolet Light Emitting Diodes (UV-LEDs) Under Thermal and Chemical Treatments - Moheb Sheikhi; Wei Guo; Yijun Dai; Mei Cui; Jason Hoo; Shiping Guo; Liang Xu; Jianzhe Liu; Jichun Ye (IEEE Photonics Journal)
In this work, the influences of thermal annealing and chemical passivation on the optical and electrical properties of ultraviolet light-emitting-diode (UV-LED) were investigated. The electroluminescence (EL) intensities of the LEDs under KOH treatment and thermal annealing increased by 48% and 81%, respectively compared to as-fabricated LED under current level of 10 mA. Cathodoluminescence (CL) mapping of UV-LEDs confirmed no variation of the density of the non-radiative recombination centers after surface treatments, and no obvious change in surface morphology was identified due to lacking of energy for surface atom migration. However, Raman spectroscopy indicates a relaxation of compressive strains inside the thin film after both thermal and chemical treatments, and conductive atomic force microscopy (c-AFM) also illustrated reduced leakage current after KOH passivation, which are responsible for the improved luminescence properties of UV-LEDs.